Inkjet-Configurable Gate Array Towards Application Specific Printed Electronic Circuits - Mashayekhi, Mohammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This thesis reports on an outstanding research advance in the development of Application Specific Printed Electronic (ASPE) circuits. It proposes the novel Inkjet-Configurable Gate Array (IGA) concept as a design-manufacturing method for the direct mapping of digital functions on top of new prefabricated structures.  The thesis begins by providing details on the generation of the IGA bulk, and subsequently presents Drop-on-Demand configurable methodologies for the metallization of IGAs. Lastly, it demonstrates IGAs' suitability for personalization and yield improvement, and reports on the integration of various circuits into IGA bulk. In addition to highlighting novel results, the thesis also offers a comprehensive introduction to printed electronics, from technology development, to design methods, tools and kits.
Introduction -- Background Asic Design Methodologies -- State Of The Art -- DesignTechnology Interaction -- Inkjet-Configurable Gate Array (Iga) -- Conclusion.
Keywords: Electronics; Electronic circuits; Engineering design; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Systems; Engineering Design